2010
DOI: 10.1002/crat.201000136
|View full text |Cite
|
Sign up to set email alerts
|

Effect of zinc doping on pentaerythritol tetranitrate single crystals

Abstract: In this study, the effect of zinc impurity on the organic high explosive pentaerythritol tetranitrate (PETN) single crystal has been investigated with optical microscopy and ex situ atomic force microscopy (AFM). The optical images show that the crystal shape has a transition with a predictable trend from long crystal to compact one as the zinc concentration is increased. Also, the 2-dimentional (2-D) growth hillocks are observed clearly on (110) face with contact AFM. The crystal growth occurs on monomolecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 32 publications
(15 reference statements)
0
4
0
Order By: Relevance
“… a The planes are sorted with respect to their surface energies, and those observed experimentally for β-HMX and PETN ,, are highlighted in bold . …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… a The planes are sorted with respect to their surface energies, and those observed experimentally for β-HMX and PETN ,, are highlighted in bold . …”
Section: Resultsmentioning
confidence: 99%
“…(b) is reprinted from ref , Copyright (2007), with permission from Springer Nature. (c) is reprinted from ref , Copyright (2010), and (e) is reprinted from ref , Copyright (2016), with permissions from John Wiley & Sons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing studies have shown that metal ions, as trace impurities, can change the crystal morphology, growth rate, and internal defects of explosives, thereby affecting their stability and, in particular, their thermal properties. [10][11][12] Xu et al 13 analyzed the influence of metal ion impurities on the crystallization and thermal properties of HMX and found that different types of metal ions have significant effects on the safety of explosives. Pitchimani et al 14 studied the morphology and activation energy of pure PETN crystals and PETN crystals doped with metal ion impurities.…”
Section: Introductionmentioning
confidence: 99%